ANALISIS HUKUM TERHADAP NILAI PEMBUKTIAN KETERANGAN ANAK SEBAGAI SAKSI DALAM PERKARA PIDANA (STUDI PUTUSAN PN. LUBUK PAKAM NO. 1482/PID.B/2015/PN.LBP) - Zefri Pandapotan Simamora; Alpi Sahari (JURNAL DOKTRIN REVIEW, 2022)
Witnesses are one of the legal means of evidence because they are used to reveal a fact. Witness statements are dug up to find the truth of criminal acts that are being examined from the investigation stage to the stage of the case examination process in court. Witness testimony given by a person who has met the requirements will not be a problem or debate, but if a witness statement is given by a child as a witness. Information from children as witnesses can have evidentiary value and can be used as legal evidence or not in court, considering that children as witnesses are not sworn in and children as witnesses are considered immature. Legal Position of Children as Witnesses in Lubuk Pakam District Court Decision No:1482/Pid.B/2015/Pn.Lbp, the age limit for child witnesses in proving as witnesses in criminal cases in the Criminal Procedure Code is that children are not yet fifteen years old and have never been married. Proof must be carried out according to valid evidence according to the law, and the judge's conviction. The testimony of a child witness is not legal evidence, but can be used as a guide, in addition to other legal evidence, and as a judge's conviction. Child protection as a witness has the right to medical rehabilitation and social rehabilitation efforts, both within the institution and outside the institution; security guarantees, whether physical, mental, or social; easy access to information about the progress of the case. Children who are in conflict with the law must be tried in a special court for children who are still in the general court environment. The process system for resolving child criminal cases in conflict with the law must be based on juvenile criminal justice procedures.